Chemical and agrochemical properties of typical rainfed sierozem soils of Uzbekistan - Kodirova Dilrabo; Safarova Nilufar; Safarov Bunyod; Turdaliev Jamolbek (BIO Web of Conferences, 2023)
The agrochemical properties of soil are important for its fertility, plant growth and development, and harvesting. In this case, humus is one of the main indicators of the total amount of nutrients. These indicators vary by soil layer. The reduction of the amount of humus in the lower layers of the soil has a negative effect on the agrophysical and agrochemical properties of the soil. Soil humus is a complex of high molecular complex chemicals consisting of protein, amino acid, wax, tar, low molecular organic acids, cellulose, lignin, chitin and other substances. Its amount is closely related to a number of factors and conditions - the amount and quality of biomass falling into the soil, the chemical composition of the soil, the environment, water-air, thermal properties, and physical-mechanical properties. This article presents information on the chemical and agrochemical status of typical rainfed sierozems. According to the results of the study, rainfed sierozems are very low in humus, low to moderate in mineral nitrogen and mobile phosphorus, moderate to high in exchangeable potassium. Carbonates are not evenly distributed along the profile of rainfed silozems, that is, some sections differ from the surface layers in their carbonate content, while in other sections, some accumulation of carbonates is observed in the middle and lower layers.